PERAN GEREJA DALAM TATA KESELAMATAN UMAT MANUSIA MENURUT ARMADA RYANTO DAN IMPLIKASINYA TERHADAP KEMANDIRIAN MARTABAT PAPUA - Tange, Yohanes Emanuel (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2026)
This article focuses on the role of the Church in the salvation of humanity according to the thought of Armada Riyanto and its implications for the autonomy and dignity of the Papuan people, with the aim of formulating a relational, dialogical and contextual ecclesiological-soteriological framework for the empowerment of the Papuan people. This research employs a qualitative literature review method, examining Armada’s works on the philosophy of relationality, interfaith dialogue, the Church in context, and the dialogical-negotiative society, which are then critically analysed in relation to theological reflections on Papuan churches and their practices amidst globalisation and the struggle for autonomy. The article’s new findings are as follows: firstly, that Armada’s understanding of salvation presupposes the Church as a dialogical-participatory community that realises salvation through liberation from all forms of violence, domination, and dehumanisation, thereby theologically demanding a commitment to the restoration of the dignity of the Papuan people. Secondly, the autonomy and dignity of the Papuan people are interpreted as a soteriological process carried out by the Church through critical faith education, social accompaniment, and transformative dialogue, rather than merely a political issue; thus, the Church is called to transform itself into a “self-reliant and dignified Papuan Church” as a free, responsible, and open historical subject engaged in dialogue with the State and various global powers.